2023
DOI: 10.21037/atm-22-6659
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-related lncRNA model based on CFAP58-DT for predicting prognosis and immunocytes infiltration in endometrial cancer

Abstract: Background: Endometrial cancer (EC) is a kind of common gynecological tumor. Further study on the markers related to the prognosis of endometrial cancer is important for women worldwide. Methods:The Cancer Genome Atlas (TCGA) database was used to obtain the transcriptome profiling and clinical data. A model was built using packages based on R software. Immune-related databases were employed to analyze the infiltration of immunocytes. Quantitative real-time PCR (qRT-PCR), cell counting kit-8 (CCK-8), and transw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
1
0
0
Order By: Relevance
“…The knockdown of CFAP58-DT lncRNA decreased the viability and migratory properties of EC cells Ishikawa and HEC-1A. In accordance with the previous studies, low and high-risk EC groups differed in the degree of immune cell infiltration; for example, the number of dendritic cells and T cells was lower in the tissues of high-risk patient tumors [171].…”
Section: Ferroptosis-based Prognostic Models Of Endometrial Cancersupporting
confidence: 89%
“…The knockdown of CFAP58-DT lncRNA decreased the viability and migratory properties of EC cells Ishikawa and HEC-1A. In accordance with the previous studies, low and high-risk EC groups differed in the degree of immune cell infiltration; for example, the number of dendritic cells and T cells was lower in the tissues of high-risk patient tumors [171].…”
Section: Ferroptosis-based Prognostic Models Of Endometrial Cancersupporting
confidence: 89%
“…They then employed Cox regression analysis to create a prognostic model for ectopic pregnancy based on these nine DEFerlncRNAs. Based on the analysis, it was found that the DEFerlncRNA prognostic model is a more effective, sensitive, and specific prognostic index in EC [ 212 ]. Furthermore, the researchers employed Gene Set Enrichment Analysis/GSEA to detect differentially expressed genes between the two groups (ecEM and euEM).…”
Section: The Existing Crosstalk Between Ferroptosis and Non-coding Rn...mentioning
confidence: 99%
“…They discovered that these differentially expressed genes are functionally enriched in a set of pathways, such as the Hedgehog signaling pathway, apoptotic flux, extracellular matrix receptor interaction, and natural killer cell-mediated cytotoxicity, along with others. For the purpose of predicting the prognosis of EC and immune-infiltrating conditions, the researchers also discovered a 9-lncRNA model, which includes CFAP58-DT (CFAP58 divergent transcript) [ 212 ]. The lncRNA in the model with the highest coefficient is CFAP58-DT , and poor EC outcomes are associated with high CFAP58-DT expression.…”
Section: The Existing Crosstalk Between Ferroptosis and Non-coding Rn...mentioning
confidence: 99%
See 1 more Smart Citation